The Influence of Promotion and Marketing via Facebook Social Media on the Volume and Sales Value of Sago Crackers - Rismawan, Yandi; Herdhiansyah, Dhian; Abdullah, Weka Gusmiarty (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2023)
Sago cracker products are only marketed from shop to shop and even from stall to stall, this is what makes Sago Cracker MSMEs still unable to market them widely. The aim of this research is to determine the effect of promotion and marketing via Facebook social media on the volume and sales value of sago crackers. Data analysis uses difference test analysis/T test. The results of the research show that the use of the Facebook marketplace feature on the sales value of Anissa sago cracker products has had a significant influence on the MSME owners of Anissa sago crackers who previously had a weekly income of IDR 960,000 before using the marketplace. Facebook and after using the Facebook marketplace, their weekly income is around IDR 1,395,000. The difference before and after using the Facebook marketplace has a real effect so that the Facebook application using the Facebook marketplace feature is effective for MSME owners to market Anissa sago cracker products. The level of consumer confidence in the sale of sago cracker products on the Facebook marketplace is 95%.